The effect of bone defect size on the 3D accuracy of alveolar bone augmentation performed with additively manufactured patient-specific titanium mesh - Wei Yang; Dan Chen; Chao Wang; Davide Apicella; Antonio Apicella; Yuanding Huang; Linzhi Li; Lingling Zheng; Ping Ji; Lizhen Wang; Yubo Fan (BMC, 2022)
Abstract Objective Additively manufactured (3D-printed) titanium meshes have been adopted in the dental field as non-resorbable membranes for guided bone regeneration (GBR) surgery. However, according to previous studies, inaccuracies between planned and created bone volume and contour are common, and many reasons have been speculated to affect its accuracy. The size of the alveolar bone defect can significantly increase patient-specific titanium mesh design and surgical difficulty. Therefore, this study aimed to analyze and investigate the effect of bone defect size on the 3D accuracy of alveolar bone augmentation performed with additively manufactured patient-specific titanium meshes. Methods Twenty 3D-printed patient-specific titanium mesh GBR surgery cases were enrolled, in which 10 cases were minor bone defect/augmentation (the planned bone augmentation surface area is less than or equal to 150 mm2 or one tooth missing or two adjacent front-teeth/premolars missing) and another 10 cases were significant bone defect/augmentation (the planned bone augmentation surface area is greater than 150 mm2 or missing adjacent teeth are more than two (i.e. ≥ three teeth) or missing adjacent molars are ≥ two teeth). 3D digital reconstruction/superposition technology was employed to investigate the bone augmentation accuracy of 3D-printed patient-specific titanium meshes. Results There was no significant difference in the 3D deviation distance of bone augmentation between the minor bone defect/augmentation group and the major one. The contour lines of planned-CAD models in two groups were basically consistent with the contour lines after GBR surgery, and both covered the preoperative contour lines. Moreover, the exposure rate of titanium mesh in the minor bone defect/augmentation group was slightly lower than the major one. Conclusion It can be concluded that the size of the bone defect has no significant effect on the 3D accuracy of alveolar bone augmentation performed with the additively manufactured patient-specific titanium mesh.